Histology of hereditary neuralgic amyotrophy. Issue 3 (16th February 2005) - van Alfen, N; Gabreëls-Festen, A A W M; ter Laak, H J; Arts, W F M; Gabreëls, F J M; van Engelen, B G M
Abstract : We report the findings in five muscle and three sural nerve biopsies, and in one postmortem plexus specimen, from six patients with hereditary neuralgic amyotrophy (HNA). We found that the sensory nerves are definitely involved in HNA despite the mainly motor symptoms, and that lesions in nerves and muscles are more widespread throughout the peripheral nervous system than clinically presumed, but, simultaneously, very focally affect isolated fascicles within individual nerves.